Risk Management for 4-H Youth Development Work: Basic Building Blocks for All - Dale Pracht; Marilyn Norman; Kate Fogarty; Jean Hink (EDIS)
4H10.2, a 3-page fact sheet by Dale Pracht, Marilyn Norman, Kate Fogarty, and Jean Hink, is part of the Risk Management for 4-H Youth Development Work series. It outlines basic overall precautions to take during 4-H activities to protect participants, sponsors, finances, and the reputation of the 4-H name. Includes references. Published by the Florida 4-H Youth Development Program, August 2010.